ASR expansions at the level of a single glass-cement paste interface: experimental results and proposal of a reaction-expansion mechanism. (10th September 2019) - Liaudat, Joaquín; Carol, Ignacio; López, Carlos M.; Leemann, Andreas
Highlights: New experimental setup for studying ASR expansions at aggregate-cement interfaces. ASR interfacial expansion curves of SL glass-cement interfaces are obtained. ASR products at the glass-cement interfaces are studied via SEM/EDS analyses. A reaction-expansion mechanism for ASR in SL glass concrete is proposed. The role of calcium: different swelling pressures of low- and high-Ca ASR products. Abstract: A new experimental methodology for studying ASR expansions at the level of a single aggregate-cementitious matrix interface is proposed. For this methodology, small sandwich-like specimens, with cement paste or mortar on top and bottom of a disc of soda-lime (SL) glass in the middle, are used. These specimens are placed in airtight containers with an alkaline solution and heated in an oven at 60 °C. In these conditions, ASR products are formed rapidly at the interface of the disc and the cementitious matrix, inducing length changes in the specimen which are measured regularly. The morphology and composition of the ASR products are studied by means of SEM/EDS analyses. This inexpensive and very easy to replicate methodology may provide valuable information about the ASR expansion mechanisms. The specimens developed expansions of about 30 μm before the SL glass got detached from the cement paste matrix. SEM/EDS analyses of the reaction products formed in between the SL glass and the cement paste matrix indicate calcium-to-silica molar ratios ranging between 1.0 and 1.5. Finally, based on the experimental results presented in this paper, as well as on other experimental and theoretical results found in the literature, a reaction-expansion mechanism for ASR in SL glass concrete is proposed.